Anatomical and histological study of kidney, ureter and urinary bladder in male guinea pig (Cavia porcellus) - Yousif, Rasha Raad; Rabee, Farhan Ouda (The Iraqi Journal of Veterinary Medicine, 2019)
A total of 20 healthy adult male guinea pigs were used in this study to investigate the anatomical, histological and morphometrical characteristics of the kidneys, ureter and urinary bladder. The gross anatomical study showed that the right kidney had a bean shape with reddish pink color whereas the left kidney had a heart shape. The renal cortex appeared darker than medulla with reddish brown color, while the medulla was pale in color. The mean thickness of cortex was more than that of medulla in both left and right kidneys and the ratio of cortex to medulla was 1.06: 1 in both kidneys. The mean length of right ureter was 10.3±0.62 cm while the mean length of left ureter was shorter. The filled urinary bladder appeared as a pear-shaped hollow sac situated in the pelvic cavity and only the rounded cranial part of bladder was expanded. Four histological regions of renal tubules were found in kidney. The Proximal convolutes tubule is first longest and coiled segment of renal tubules which originate from urinary pole of renal corpuscles and measured about 25.421±0.3µm in diameter and lined with simple cuboidal epithelial cells. The Nephron loop (Loop of Henle) was consisted of the descending and ascending thin limbs, the descending thin limb was measured 13.591±0.1µm diameter, whereas the thick ascending limb was measured (19.987±0.5µm) in diameter. Distal convolutes tubule was shorter than the proximal tubule and measured about 21.139±0.5µm diameter. The collecting duct was measured about (31.759±0.2µm) diameter. It was lined with simple cuboidal or columnar epithelium. The cross section of Ureter was possessed a star shape lumen and its wall consist from four tunics (mucosa, lamina propria submucosa, muscularis and serosa). It was lined by transitional epithelium. The histological structure of Urinary Bladder was resembles the ureter, the lamina propria contain few mucous glands.